The impact of trade liberalization on developing countries' trade balance with industrial and developing countries: an econometric study - Mat Ghani, Gairuzazmi (Universiti Malaysia Sarawak, 2009)
This paper examines the impact of trade liberalization on the merchandise trade balance for a sample of developing countries that have adopted trade liberalization policies. The impact is differentiated according to the destinations and origins of the exports and imports, whether they are developing or industrial countries. This is important as one of the arguments for protection is based on the assumption of asymmetry in the elasticities of products traded between developing and industrial countries, and this asymmetry leads to disparity in economic growth. The paper shows that the impact on the merchandise trade balance differs between the two groups of trading partners; there is weak evidence that the trade balance worsens (increase in deficit) for trade with developing countries, but the trade balance improves (increase in surplus) for trade with industrial countries.